Perancangan Sistem Informasi Survei Kepuasan Pengguna Layanan Berbasis Website untuk Penjaminan Mutu Internal di FMIPA UNJ - Qoonitah Putri, Maura (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2022)
The Internal Quality Assurance System (SPMI) is an effort by universities to improve their quality standards continuously. As one of the universities, Universitas Negeri Jakarta (UNJ) seeks to improve quality assurance by forming a Quality Assurance Unit (SPM) to compile satisfaction instruments in the form of questionnaires based on 9 criteria as a survey method for benchmark assessment of satisfaction levels of service at FMIPA UNJ and as an internal evaluation material for quality improvement. In answering the problems found, the purpose of this study was to design a Web-based User Satisfaction Survey Information System for Internal Quality Assurance at FMIPA UNJ to facilitate the filling of surveys, management of satisfaction instruments and survey results data conducted by the FMIPA UNJ Quality Assurance Group (GPjM). The system was developed using the SDLC (System Development Life Cycle) software development method with the Spiral Model. In system coding is used the concept of MVC (Model View Controller). At the end of system development, developers test the system using theBlack Box approach before the app is launched to the user by checking each component of the application's features independently and one by one. The final stage of testing used User Acceptance Testing (UAT) is a website exposed to the actual user to be tested for functional specifications of the system and usability of the system. Obtained the results of the functionality test worth 94.6%, it was concluded that the features contained in the entire system can be categorized very in accordance with the expected results, while the use test obtained results worth 91%, inferred the value of usefulness on the whole system received a very decent predicate.